Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.19184/ikesma.v14i1.10401
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Dan Sikap Terhadap Kepatuhan Minum Obat Pasien Tuberkulosis Paru Fase Lanjutan Di Kecamatan Umbulsari Jember

Abstract: Tuberkulosis (TB) is a infectious disease caused by t Mycobacterium Tuberculosis. Indonesia is the second country with highest number of TB cases in the world after India. Medication adherence is essential for successful TB treatment. One of the factors that can influence someone adherence to TB treatment is knowledge and attitude. This study aimed to know the correlation between knowledge and attitude towards the adherence of medication in tuberkulosis pulmonary patient on continuation phase in umbulsari jemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
1
1
0
7
Order By: Relevance
“…Based on the study results, it was also found that there was no relationship between the level of knowledge of students majoring in nursing about COVID-19 and the compliance of students majoring in nursing in taking preventive measures against COVID-19. These results follow previous studies that showed no significant relationship between the level of knowledge and patient compliance in taking medication (17).…”
Section: Resultssupporting
confidence: 92%
“…Based on the study results, it was also found that there was no relationship between the level of knowledge of students majoring in nursing about COVID-19 and the compliance of students majoring in nursing in taking preventive measures against COVID-19. These results follow previous studies that showed no significant relationship between the level of knowledge and patient compliance in taking medication (17).…”
Section: Resultssupporting
confidence: 92%
“…Mycobacterium tuberkulosis yang sebagian besar menyerang paru-paru 1 , namun juga dapat menyerang organ tubuh lainnya seperti selaput otak, kelenjar getah bening, kelenjar limfe, ginjal, pleura, telinga bagian tengah, usus, tulang belakang, tenggorokan mata dan kulit 2 . Pengetahuan yang dimiliki pasien menjadi salah satu faktor yang dapat mempengaruhi terjadinya kegagalan terapi selain peran pengawas minum obat, dukungan keluarga, akses transportasi dan jarak dari tempat tinggal pasien menuju tempat pelayanan kesehatan, motivasi dan efek samping yang dirasakan 3,4 . Kepatuhan diartikan sebagai tingkatan seseorang dalam berperilaku untuk memperoleh keberhasilan pengobatan, diet dan melakukan gaya hidup yang sesuai dengan rekomendasi dari pelayanan kesehatan 5,6 .…”
Section: Tuberkulosis (Tb) Merupakan Penyakit Menular Yang Disebabkan...unclassified
“…Artikel lain yang menunjukkan bahwa edukasi kepada pasien TB menunjukkan ada hubungan pengetahuan dengan kepatuhan pada tingkatan tahu. Namun ternyata tidak ada korelasi antara pengetahuan dengan kepatuhan pada tingkatan paham dan pada sikap pasien TB (Mientarini, Sudarmanto and Hasan, 2018). Inilah yang menjadi problem utama penggunaan obat TB.…”
Section: Pendahuluanunclassified
“…Terjadi perbaikan pada perilaku 21 orang responden yang diberi edukasi tentang kesehatan, berbeda dengan 21 orang lainnya yang ada dalam keompok kontrol (Rizana, Tahlil and Mulyadi, 2016), meskipun ada juga beberapa penelitian yang menunjukkan kalau pengetahuan yang baik tidak selalu membuat pasien patuh minum obat (Mientarini, Sudarmanto and Hasan, 2018). Pasien dan keluarganya yang sudah mendapat edukasi telah meningkat pengetahuan dan sikapnya.…”
Section: Pemberian Bahan Complementer Medicineunclassified